Practical Groovy programming : essential techniques for working with JSON, metaprogramming, the Groovy JDK, and SQL - Kousen, Kenneth A.; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Take your basic Groovy skills to the next level with this practical video workshop. Presenter and Java consultant Ken Kousen shows you how to work with XML and JSON, implement runtime metaprogramming, and use several AST transformations. You'll also dive into operator overloading, Groovy SQL, and the Groovy JDK. Once you complete this course, check out Ken's other videos on the subject: Mastering Groovy and Groovy Fundamentals. These courses demonstrate the many advantages of adding Groovy to existing projects written in Java and other object-oriented languages."--Resource description page.
Title from resource description page (Safari, viewed July 7, 2015).
Date of publication taken from end of first video slide (Safari, viewed July 7, 2015).
Presenter, Ken Kousen.
Keywords: Groovy (Computer program language); Electronic books